A Book Review of Global Perspectives on Project-Based Language Learning, Teaching, and Assessment: Key Approaches, Technology Tools, and Frameworks - Febriyani Febriyani; Febrina Dafit; Sri Wahyuni (MASI Mandiri Edukasi, 2025)
This review focuses on the book Global Perspectives on Project-Based Language Learning, Teaching, and Assessment: Key Approaches, Technology Tools, and Frameworks, edited by Gulbahar H. Beckett and Tammy Slater. The book provides an in-depth discussion of project-based language learning (PBLL) and emphasizes the role of technology-enhanced learning. Using a structured analytical framework, it explores foundational theories, practical applications, and technology-driven strategies to advance language acquisition, critical thinking, collaboration, and global competencies. Organized into three parts, the book covers philosophical and theoretical insights, empirical studies on technology-integrated PBLLs, and practical frameworks for using technology in language education. This review critically evaluates the chapters' coherence, theoretical grounding, and pedagogical relevance. It highlights the book's significant contributions, emphasizing their value to educators, researchers, and practitioners by offering novel, technology-focused solutions to prepare learners for the challenges of the 21st century.